Beyond Dordt and 'De Auxiliis' : the dynamics of protestant and catholic soteriology in the sixteenth and seventeenth centuries - Ballor, Jordan J. (Jordan Joseph); Gaetano, Matthew T.; Sytsma, David S. (Studies in the history of Christian traditions ;, 2019)
Beyond Dordt and 'De Auxiliis' explores post-Reformation inter-confessional theological exchange on soteriological topics including predestination, grace, and free choice. These doctrines remained controversial within confessional traditions after the Reformation, as Dominicans and Jesuits and later Calvinists and Arminians argued about these critical issues in the Augustinian theological heritage. Some of those involved in condemning Arminianism at the Synod of Dordt (1618-1619) were inspired by Dominican followers of Thomas Aquinas in Spain who had recently opposed the vigorous defense of free choice by Jesuit Molinists in the Congregatio de auxiliis (1598-1607). This volume, appearing on the 400th anniversary of the closing of the Synod of Dordt, brings together a group of scholars working in fields that only rarely speak to one another to address these theological debates that cross geographical and confessional boundaries.